Processing of information in social investigations - Beatriz Bú-Alba; Amelia Patricia Silva-Bravo; Nelson Arias-Saumell (Maestro y Sociedad, 2018)
This work has the purpose of achieving an approach to the particularities of data processing of social investigations; as well as a brief reference to the use of Information and Communication Technologies as a support tool, through consultation with authorized theoretical sources. The methodological strategy was systematized through hermeneutics, bibliographic revision and deduction, which allowed us to conclude that: current studies point to the recognition of quantitative-qualitative relationships, reject the extreme dichotomy between these paradigms; multiple approaches are recognized for the development of qualitative research; there is a close relationship between the stages of planning, collection, processing and analysis of data.